Accessibility issues of persons with disabilities due to COVID-19 pandemic in Nagpur region - Gawande, Avinash; Raut, Abhijit V.; Pusam, Sanjay; Prabhune, Trupti (International Journal Of Community Medicine And Public Health, 2021)
Background: Since the first case of COVID-19 in late January 2020, India has become one of the hardest hit countries by COVID-19 in world. According to 2011 census, the number of PwDs in India is roughly 2.2% of total population which is approximately 26.8 million. They are more vulnerable to COVID-19 infection due to their disability and lack of accessibility to protect them. Methods: A cross sectional, mixed-methods approach, using a purposive sampling technique, a quantitative survey were adopted for the study. Results: The study showed that 99% of the participants have access to regular updated knowledge of COVID-19. 74% participants faced scarcity of protective measures, 35% faced scarcity of ration supply, 48% PwDs faced major issues to access screening, testing and treatment facilities in suspected COVID-19 cases. 43% PwDs faced scarcity of access to assistive services and devices. 40% faced issues to get their regular medicines and necessary items like catheters. 86% of the participant faced financial crises due to loss of employment and businesses. Around 16% amongst them faced severe crises which was not possible to manage. Conclusions: Facing COVID-19 situation is extremely stressful for PwDs. This study was conducted for short period of 4 months so it gives a snapshot of impact of COVID-19 on accessibility issues of PwDs.